Komunikasi Islam dalam Harmoni Keberagaman di Jawa Timur - Agoes Moh. Moefad; Maulidatus Syahrotin Naqqiyah; Barokatun Nuris Syah Riyah (Institut Agama Islam Tribakti (IAIT) Kediri, 2023)
This research reveals about Islamic communication in building harmony in the diversity of society. The harmony of diversity in this case is intended to neutralize phenomena in society that are